Charge reversal and surface charge amplification in asymmetric valence restricted primitive model planar electric double layers in the modified Poisson-Boltzmann theory - Bhuiyan, L.B.; Outhwaite, C.W. (Condensed Matter Physics, 2017)
The modified Poisson-Boltzmann theory of the restricted primitive model double layer is revisited and recast in a fresh, slightly broader perspective. Derivation of relevant equations follow the techniques utilized in the earlier MPB4 and MPB5 formulations and clarifies the relationship between these. The MPB4, MPB5, and a new formulation of the theory are employed in an analysis of the structure and charge reversal phenomenon in asymmetric 2:1/1:2 valence electrolytes. Furthermore, polarization induced surface charge amplification is studied in 3:1/1:3 systems. The results are compared to the corresponding Monte Carlo simulations. The theories are seen to predict the “exact” simulation data to varying degrees of accuracy ranging from qualitative to almost quantitative. The results from a new version of the theory are found to be of comparable accuracy as the MPB5 results in many situations. However, in some cases involving low electrolyte concentrations, theoretical artifacts in the form of un-physical “shoulders” in the singlet ionic distribution functions are observed. В роботi переглядається i представляється у новому, бiльш широкому свiтлi модифiкована теорiя Пуасона-Больцмана (МТПБ) обмеженої примiтивної моделi подвiйного шару. На основi попереднiх формулювань МТПБ4 i МТПБ5 виводяться вiдповiднi рiвняння, якi дозволяють краще зрозумiти зв’язок мiж цими формулюваннями. МТПБ4, МТПБ5 i нове формулювання теорiї застосовуються для аналiзу структури i явища змiни знаку заряду в електролiтах з асиметричною валентнiстю 2:1/1:2. Вивчається також явище iндукованого поляризацiєю збiльшення поверхневої густини заряду у системах 3:1/1:3. Проводиться порiвняння з даними моделювання методом Монте-Карло. Показано, що наведенi теорiї вiдтворюють данi моделювання з рiзним ступенем точностi вiд якiсного до майже кiлькiсного. Результати нового варiанту теорiї в багатьох випадках практично не вiдрiзняються вiд результатiв МТПБ5. Однак при певних умовах, зокрема при низьких концентрацiях електролiтiв, спостерiгаються теоретичнi артефакти у формi нефiзичних “плечей” в унарних функцiях розподiлу iонiв.